Motivations for moving among Commercial Counterurbanisers - Gary Bosworth (European Regional Science Association (ERSA), 2011)
This paper reports on findings from business surveys and face to face interviews conducted in the North East and East Midlands regions of the UK. Previous studies into residential counterurbanisation have shown a range of factors influencing individuals' choices to move house. Here, it is hypothesised that for some commercial counterurbanisers, those rural in-migrants running businesses in their new rural locality, there will be different influences. Focusing on two groups of commercial counterurbanisers, the planned and un-planned business starters, it is also hypothesised that the different expectations and influences will affect their subsequent perceptions of the rural area as a place to do business. Greater understanding of the characteristics of place that are attractive to business starters and latent entrepreneurs can guide spatial economic policy which has become increasingly concerned with "place competitiveness" (Bristow, 2011).
Keywords: 330; Commercial Counterurbanisation; entrepreneurship; place competition; competitiveness; rural business; rural economy